Artrópodos (Arthropoda: Arachnida e Insecta) asociados a los nidos de Neotoma mexicana (Mammalia: Rodentia) de San Miguel de Allende, Guanajuato, México - Martínez-Hernández, Mariana S.; Hernández-Hernández, Zaira; Villegas-Guzmán, Gabriel A.; Gaona-Ramírez, Salvador (Instituto de Ecología, A.C., 2019)
The nests of rodents are the refuge of different species of arthropods such as mites, fleas, bugs, lice, and pseudoscorpions, among others. Some of them are of veterinary and medical importance because they are vectors of diverse diseases that can be transmitted to a human, domestic and wild animals. A nest of Neotoma mexicana was collected, from which 148 arthropods of four orders were found: Acari, Pseudoscorpiones (Arachnida), and Siphonaptera (Insecta). The most abundant species of mites was Cheyletus eruditus (Acari: Prostigmata: Chayletidae) with 126. Tectocepheus velatus (Acari: Oribatida: Tectocepheidae) is a new record for Neotoma nests. The pseudoscorpions represent the first records for Guanajuato, being Parachernes a new record for this microhabitat. Whilst for the order Siphonaptera Tunga monositus is a new record for Guanajuato.